If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(c + 3t) = x (c * 4 + 3t * 4) = x (4c + 12t) = x Solving 4c + 12t = x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-12t' to each side of the equation. 4c + 12t + -12t = -12t + x Combine like terms: 12t + -12t = 0 4c + 0 = -12t + x 4c = -12t + x Divide each side by '4'. c = -3t + 0.25x Simplifying c = -3t + 0.25x
| 2(x-2)-54=7x-5(x+6) | | 5c^2+10x=0 | | 25=4x^2-5x-50 | | x+iy^2=-5+12i | | .09(x+5)=28 | | 3+.20x=.40 | | 11x+y=-13 | | -15-2p=1+6p | | 5+18z-2=9z+123-6z | | 8=-7t-(-8) | | 3x+12=z | | 20=l+2w | | 125*125*125-6=0 | | 2.5x-x=6 | | 12x-4=14x-8 | | 240x+360y=3000 | | 3x-5=5x-5 | | 15x-15y=-64 | | 9x^2+72=0 | | 7k^2-14k-17=4 | | a-z=6 | | 2.5x=x+6 | | 10+2n=1 | | 22=9-x | | 4+p-4=-1+2p | | -3x+15-5=39 | | 6m+15=17 | | 5*-0.06= | | 15x-15y=64 | | 3(t-4)+5t=4(2t+3)-9 | | 3w+13=49 | | 12x+4-78=3-13 |